For two vectors A and B where A = a1*i + b1*j + c1*k and B = a2*i + b2*j + c2*k, the cross product AxB is given by (b1*c2 - c1*b2)i - (a1*c2 - c1*a2)j + (a1*b2 - b*a2)k

AXB is not equal to BxA, but AxB = -BxA

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

For two vectors A and B where A = a1*i + b1*j + c1*k and B = a2*i + b2*j + c2*k, the cross product AxB is given by (b1*c2 - c1*b2)i - (a1*c2 - c1*a2)j + (a1*b2 - b*a2)k

AXB is not equal to BxA, but AxB = -BxA

For the vectors A = 6i + 3j + 4k and B = 2i + 3j + k

AxB = (3*1 - 4*3)i - (6*1 - 4*2)j + (6*3 - 3*2)k

=> -9i +2j +12k

BxA = (3*4 - 1*3)i - (2*4 - 1*6)j + (2*3 - 3*6)k

=> 9i -2j -12k

**The required cross products are AxB = -9i +2j +12k and BxA = -9i +2j +12k**